Prediction of Corpse Model Drifting Trajectories in Pearl River Front Channel Based on Delft3D Model - CHENG Xiangju; CHEN Zehai; LI Bin; LI Xu; BI Jinjin; WANG Longwei (Renmin Zhujiang)
To predict the drifting trajectories of bodies in the Pearl River Front Channel and assist local water police in locating the specific positions of drowning victims, this study uses Delft3D to construct a hydrodynamic model of the Pearl River Front Channel and conducts multiple on-site drifting tests using a corpse model. By fitting the surface flow velocity of the Pearl River Front Channel, the paper builds a prediction model for corpse model drifting with an R2 of 0.88. The results show that the corpse model released in the Pearl River Front Channel undergoes back-and-forth motion along the river channel under the influence of tides and flows, gradually drifting downstream. In the drifting model validation, the drifting speed and direction of the corpse model are generally consistent with the tidal current, and the error in simulation results is within 1 km, with a final distance error rate of less than 15%. In a case study, the simulated results for an adult female corpse have an error of approximately 300 m. External forces such as wave force caused by boats result in a north-south directional deviation in the drifting trajectory, indicating the need to further improve the simulation effect. The derivation mode of the model is also applicable to other tidal rivers, making it possible to measure the drifting trajectories of bodies and providing convenience and reference for body recovery work and police case processing.